Pyroptosis-Related Risk Signature Exhibits Distinct Prognostic, Immune, and Therapeutic Landscapes in Hepatocellular Carcinoma - Zhao, Yidi; Song, Qingya; Xu, Fangshi; Zhou, Yang; Zuo, Xiaoli; Zhang, Zhengliang (Frontiers in Genetics, 2022)
Background Hepatocellular carcinoma (HCC) is a common abdominal cancer. The existing therapeutic approaches often fail to achieve satisfactory results. Pyroptosis, an inflammatory form of programmed cell death, provides new ideas for anti-cancer treatment. However, the roles of pyroptosis-related (PR) genes (PRGs) in HCC remain elusive. Methods The differentially expressed genes (DEGs) (n=22) were screened out using TCGA and GTEx databases. The novel PR risk signature was constructed through the Lasso regression analysis. Its prognostic value was evaluated through a series of survival analyses and was tested in ICGC and GSE14520 cohorts. CIBERSORT, ssGSEA and ESTIMATE methods were employed to determine the effects of PR risk score on tumor immune microenvironment (TIM). TIDE scoring system, IMvigor210 cohort, GSE109211 dataset and GSDC database were applied to explore the associations of PR risk score with therapeutic effects. The biofunctions of WNK1 in hepatocellular cancer (HC) cells were confirmed through qPCR, colony formation, and Tranwell assays. Results 22 of 45 PRGs (48.9%) were abnormally expressed in HCC samples. Then, a PR risk signature consisting of 8 PRGs was constructed. High PR risk score led an unfavorable prognosis. PR risk score was identified as an independent prognostic factor of HCC and could increase the making-decision benefit of traditional TNM model. Besides, we established a nomogram containing clinical stage and PR risk score to predict the survival rates of HCC patients. The prognostic value of PR model was successfully validated in ICGC and GSE14520 cohorts. Moreover, high PR risk conferred the decreased infiltration level of CD8+ T cells and weakened the activities of ‘Cytolytic activity’ pathways. As for therapeutic correlation, high PR risk score seemed to imply a poor efficacy of PD-1/L1 inhibitors and sorafenib. Finally, overexpression of WNK1 could promote the proliferation, migration, and invasion of HC cells. Conclusions PR risk score was closely related to the prognosis, anti-tumor immune process, therapeutic outcomes, and malignant progression of HCC. WNK1, the core regulator of pyroptosis, possesses pro-oncogenic abilities, showing promise as a novel treatment target.